The sustainable housing question: On the role of interpersonal, impersonal and professional trust in low-carbon retrofit decisions by homeowners. (May 2019) - de Wilde, Mandy
Abstract: Trust is critical for facilitating energy transitions in both general and market exchange, and most particularly in consumer engagement. However, little research has been done to demonstrate how trust is established and how it influences the decision-making process of important change agents in energy transitions. On the basis of 40 in-depth interviews with homeowners who adopted a domestic low-carbon retrofit measure, this paper distinguishes three modes of trust that play a role in a retrofit decision-making process. First, interpersonal trust builds on the familiarity and social identification within social networks. Second, impersonal trust develops through certified tools and standards generated by governmental bodies and other actors perceived as independent. Finally, professional trust arises due to the perceived professional capacities and ethics of supply-side actors in the construction industry, and insulation and installation businesses. The paper demonstrates the various roles that modes of trust have in the decision-making process. Moreover, the paper shows the interaction between these different modes of trust and their mediators. Tailoring domestic low-carbon retrofit campaigns and services to different modes of trust is imperative in order to persuade homeowners to retrofit their homes, to engage with energy issues and to contribute to a transition to sustainable housing.